Integrating PjBL to foster edupreneurship: A biology innovation module for senior high school - Risti Wiludjeng Muljasari; Nur Kuswanti; Y. Yuliani (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Science curricula often fail to bridge theoretical knowledge with entrepreneurial skills. This research aimed to develop and assess a Project-Based Learning (PjBL)-integrated teaching module designed to foster edupreneurship in biology technology innovation among Senior High School students. This study employed a systematic Research and Development (R&D) approach using the ADDIE model. This article specifically details the analysis, design, and development phases. The module's validation results, assessed by two expert lecturers, indicated it was "Very Valid" across all aspects. The practicality assessment, conducted with two Biology teachers, categorized the module as "Very Practical" overall. A readability test using the Fry Readability Score yielded an average reading grade level of 10-11, which is highly appropriate for the target 10th-grade Senior High School students. These findings collectively underscore the module's high quality, contextual relevance, and readiness for implementation, demonstrating its significant potential to enhance both scientific literacy and an entrepreneurial mindset among Senior High School students.